The impact of sprint, middle-distance, and long-distance orienteering races on perceived mental fatigue in national level orienteers - Lam, H. K. N.; Sproule, J.; Turner, A. P.; Phillips, S. M. (Journal of Sports Sciences, 2023)
Experiencing mental fatigue (MF) before an orienteering race can lead to a slower completion time. This study aimed to explore the changes in perceived MF, mood and other psychological responses during an orienteering competition. Sixteen national level orienteering athletes (20.8 ± 4.9 years) provided informed consent and completed the online surveys, before and immediately after each race, and 24- and 48-hours post competition (48POST). This study measured MF, physical fatigue, stress, tiredness and motivation using 0-100 Visual Analogue Scale, and the mood was assessed using The Brunel Mood Scale (BRUMS). A moderate to large increase in MF (ES = 0.93 [0.54 to 1.31]), BRUMS fatigue (ES = 0.61 [0.3 to 0.92]), and PF (ES = 1.21 [0.81 to 1.61]) was reported following orienteering races. A small increase in tiredness and BRUMS confusion, and a small decrease in motivation, stress and BRUMS vigour was also reported. There was a delay in recovering from the MF elicited by competition, with a small increase in MF (ES = 0.54 [0.08 to 1.15]) at 48POST compared to the pre-competition value. This study found that orienteers experience MF during competition and have a delayed recovery that can last up to two days after the competition.